(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article says that the bank guarantee plays an important role in establishing and strengthening economic relations between partners, developing and developing trade, organizing the production and service process, formalizing various economic contracts, organizing and implementing export-import operations, generating credit relations, participating in tender sales, as well as establishing new cooperation between business entities.